If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3(x + -4) = 2(2 + -3) Reorder the terms: 2x + 3(-4 + x) = 2(2 + -3) 2x + (-4 * 3 + x * 3) = 2(2 + -3) 2x + (-12 + 3x) = 2(2 + -3) Reorder the terms: -12 + 2x + 3x = 2(2 + -3) Combine like terms: 2x + 3x = 5x -12 + 5x = 2(2 + -3) Combine like terms: 2 + -3 = -1 -12 + 5x = 2(-1) Multiply 2 * -1 -12 + 5x = -2 Solving -12 + 5x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 5x = -2 + 12 Combine like terms: -12 + 12 = 0 0 + 5x = -2 + 12 5x = -2 + 12 Combine like terms: -2 + 12 = 10 5x = 10 Divide each side by '5'. x = 2 Simplifying x = 2
| 6(x-5)-(4x+4)=-1 | | (3/2)x^2-6x=0 | | 5-6x=45-5x | | 4(z+3)=(2z+3) | | 9a-6=12+3 | | 3(4)+3(2+7)=(x)x(4+9) | | x/2-8=-6 | | 8=ba | | x+7+6x-24=24 | | 8x+y=-16-3x=y=-5 | | (5x-5)(5x-5)=0 | | 8x-3x+2-x=4x+5 | | 8x-3x+2-x=3x+4 | | 8x-3x+2-x=2x+3 | | 3(2b+7)2=75 | | 27x^2k=3x^5 | | 2(x+y)=7y-5 | | 11r-2(-12r-1)=3(4r-7) | | 9a-8=5a | | 15s+30=90 | | 8x-3x+2-x=8x+9 | | 14l+7=133 | | -4x+5=-7 | | 18x(15x)= | | 14l+1=133 | | 10a-3a=-2(4+8a)+5(12+2a) | | 2(x+6)=9x+8-7x+4 | | 3a-12=54 | | z^2-11z=-10 | | 5x=6(38.5-x) | | 8x-3x+2-x=3x+8 | | 2*sin*3*x=0 |